KONSELING PASTORAL SEBAGAI PENDAMPINGAN BAGI PEMUDA YANG SULIT KELUAR DARI TOXIC RELATIONSHIP DALAM PACARAN - Lalompoh, Suryaningsi Dorthea; Londo, Elsye Esterina (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
This research is motivated by a common phenomenon, namely the occurrence of toxic relationships in dating relationships. Toxic relationships that should be immediately repaired or ended, but in reality many persist and find it difficult to get out of these relationships, one of which happened to three Christian youths in Sangihe Islands Regency. Based on the research conducted, it was found that the reason they find it difficult to get out and therefore stay in a toxic relationship is because they are emotionally dependent, feel great love for their partner, hope that their partner will change, are easily persuaded by their partner, and imagine a relationship that has existed for a long time. By choosing to stay in this relationship, there are negative impacts experienced, namely affecting the young man's physical, psychological, spiritual health and social situation. Based on this problem, it is very important to carry out pastoral counseling as an effort to provide assistance to young people who have difficulty getting out of toxic relationships. This is important because young Christians need to continue to receive attention from the church, because they are the backbone of the church. So that the caring and caring attitude of the church can be realized through pastoral counseling to help them get through this period by providing understanding so that they can make the right decisions, experience recovery from all the wounds they have experienced, and experience peace.